2002
DOI: 10.1107/s0907444901021758
|View full text |Cite
|
Sign up to set email alerts
|

Atomic resolution structures of ribonuclease A at six pH values

Abstract: The diffraction pattern of protein crystals extending to atomic resolution guarantees a very accurate picture of the molecular structure and enables the study of subtle phenomena related to protein functionality. Six structures of bovine pancreatic ribonuclease at the pH* values 5. 2, 5.9, 6.3, 7.1, 8.0 and 8.8 and at resolution limits in the range 1.05±1.15 A Ê have been re®ned. An overall description of the six structures and several aspects, mainly regarding pH-triggered conformational changes, are describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
96
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(102 citation statements)
references
References 39 publications
5
96
0
1
Order By: Relevance
“…It is gratifying to notice that both solid state and solution data converge in the indication that the leucine side chain perturbs the lysine native conformation, thus strengthening the indication that this is a genuine feature of the mutant. A similar subtle modification of the side chain conformation of the catalytic Lys 41 was observed in RNase A and was suggested to be important in the substrate binding (41) and in the pH modulation of the enzyme activity (40,46). In the same enzyme a very subtle shift of the active site His 119 was considered to affect the catalytic activity of some mutants of the pancreatic enzyme (47).…”
Section: X-ray Structure Of M23l-onc and (C87sdes103-104)-onc-mentioning
confidence: 82%
“…It is gratifying to notice that both solid state and solution data converge in the indication that the leucine side chain perturbs the lysine native conformation, thus strengthening the indication that this is a genuine feature of the mutant. A similar subtle modification of the side chain conformation of the catalytic Lys 41 was observed in RNase A and was suggested to be important in the substrate binding (41) and in the pH modulation of the enzyme activity (40,46). In the same enzyme a very subtle shift of the active site His 119 was considered to affect the catalytic activity of some mutants of the pancreatic enzyme (47).…”
Section: X-ray Structure Of M23l-onc and (C87sdes103-104)-onc-mentioning
confidence: 82%
“…Indeed the torsion angles about the virtual bonds, given in Table III, clearly show the similarity of the peptide conformation with the F conformation of the native enzyme. For comparison, the values of angles for an unswapped conformation of the hinge peptide is also given; since this peptide is disordered in both MϭM (6) and in the monomeric derivative of BS-RNase (29), the conformational parameters presented in Table III are those of RNase A refined at atomic resolution at pH 5.9 (PDB code 1KF3) (31). The hinge peptide of this protein is also shown in Fig.…”
Section: Domain Swapping In Bovine Seminal Ribonucleasementioning
confidence: 99%
“…The D 1 atom of His119 is hydrogen bonded to the oxygen of O89 (2.3 Å), while the D 2 atom of His119 is hydrogen-bonded to the O 1 atom of Asp121. It was reported that at pH 6.3, the active site has a sulphate ion, which is hydrogen bonded to the ordered His119, whereas at pH 7.1 the active site releases the sulphate ion and has a disordered His119 (Berisio et al 2002). Although a soaking solution at pD 6.2 was used in this study, the active site does not have the sulphate group, and His119 is ordered.…”
Section: Rnase Amentioning
confidence: 99%
“…To act as a base, His12 should be singly protonated. However, double protonation of His12 at acidic pH has been reported from both X-ray and neutron diffraction analyses (Berisio et al 2002;Wlodawer et al 1983;Wlodawer et al 1986). Neutron diffraction analysis suggested at first glance that His12 is doubly-protonated (positively charged) (Usher et al 1972).…”
Section: Rnase Amentioning
confidence: 99%
See 1 more Smart Citation